Nutritional Status of Dalit Children: A Comparative Study with Non-Dalit Children in Eastern Terai of Nepal - Kafle, Tara Kumari; Singh, GP; Singh, SP; Kafle, TK (Birat Journal of Health Sciences, 2017)
IntroductionThe poor nutritional status of under five children has been considered a serious problem in Nepal for many years. Children need adequate nutrition for their proper physical, emotional as well as psychological development.ObjectiveThe objective of this study was to assess and compare the nutritional status of under five children and explore its socio demographic determinants.MethodologyAn analytical cross-sectional study was conducted in Eastern Terai, ecological belt of Nepal. Predesigned, pretested interview schedule was used to collect the information. Information was collected from 720 Dalit as well as Non-dalit mothers about their youngest children. The nutritional status was measured byusing anthropometric measurements.  ResultsIn bi-variate analysis the significant difference were observed among children's nutritional status between castes as well as a number of socio-demographic variables however in multivariate analysis only caste, number of Children Ever Born (CEB) and mother's education were found significant determinants of height for age, mother's education was found significant determinant for weight for height and caste, age of children and mother's education were found significant determinants of weight for age of children.ConclusionDalit children were found much more malnourished than Nondalit. The castes, age of child, CEB to mother and mothers' education were found as the determinants of nutritional status among under-five children.Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 117-126